1993
DOI: 10.1038/ng0793-314
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a common mutation in the carnitine palmitoyltransferase II gene in familial recurrent myoglobinuria patients

Abstract: Carnitine palmitoyltransferase (CPT) II deficiency is the most common inherited disorder of lipid metabolism affecting skeletal muscle. We have identified a missense mutation (Ser113Leu) in one patient with the classical muscular symptomatology. Transfection experiments in COS cells demonstrate that the mutation drastically depresses the catalytic activity of CPT II. The mutation results in normal synthesis but a markedly reduced steady-state level of the protein, indicating decreased stability of mutant CPT I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
97
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 189 publications
(103 citation statements)
references
References 27 publications
6
97
0
Order By: Relevance
“…Taroni et al [lo41 designate this allele ILV. Whereas the presence of the two polymorphisms on the mutant allele appeared not to affect the low residual activity of the protein when expressed in COS cells, it exacerbated the deleterious impact of a second disease-causing mutation identified in an infantile case of CPT I1 deficiency as Arg631Cys [104]; the authors refer to the latter defective allele as ICV. One of the 25 adult patients studied in [lo41 proved to be a compound heterozygote carrying both ILV and ICV mutant alleles.…”
Section: Structurementioning
confidence: 99%
See 3 more Smart Citations
“…Taroni et al [lo41 designate this allele ILV. Whereas the presence of the two polymorphisms on the mutant allele appeared not to affect the low residual activity of the protein when expressed in COS cells, it exacerbated the deleterious impact of a second disease-causing mutation identified in an infantile case of CPT I1 deficiency as Arg631Cys [104]; the authors refer to the latter defective allele as ICV. One of the 25 adult patients studied in [lo41 proved to be a compound heterozygote carrying both ILV and ICV mutant alleles.…”
Section: Structurementioning
confidence: 99%
“…Particularly common among European subjects with the classical adult muscular form of the disorder is a C-T transition at nucleotide 439 which changes amino acid 113 from serine to leucine. In 25 such patients, all unrelated, the Serll3Leu mutation was found on 28 of the 50 mutant alleles, but in none of 31 unaffected control subjects [104]. Curiously, in all cases the defective allele also contained two polymorphic variants, Va1368Ile and Met647Va1, which occur in the general population with allele frequencies of 0.51 and 0.25, respectively [104].…”
Section: Structurementioning
confidence: 99%
See 2 more Smart Citations
“…Truncating CPT II mutations are often associated with the severe neonatal form, while "mild" missense mutations mostly lead to the infantile or adult form. The most common mutation in (adult) CPT II deficiency is the S113L substitution (Taroni et al 1993), while several other mutations have also been identified in individual patients suffering the late-onset and infantile forms. But to date, only four individual mutations, all located in the CPT II gene, have been found in patients with the neonatal form of CPT II deficiency (Bonnefont et al 1999).…”
Section: Introductionmentioning
confidence: 99%